Proceedings of the 2015 Conference on Empirical Methods in Natural Language Processing 2015
DOI: 10.18653/v1/d15-1141
|View full text |Cite
|
Sign up to set email alerts
|

Long Short-Term Memory Neural Networks for Chinese Word Segmentation

Abstract: Currently most of state-of-the-art methods for Chinese word segmentation are based on supervised learning, whose features are mostly extracted from a local context. These methods cannot utilize the long distance information which is also crucial for word segmentation. In this paper, we propose a novel neural network model for Chinese word segmentation, which adopts the long short-term memory (LSTM) neural network to keep the previous important information in memory cell and avoids the limit of window size of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
237
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(239 citation statements)
references
References 29 publications
2
237
0
Order By: Relevance
“…We replace the discrete word and character features of Zhang and Clark (2007) with word and character embeddings, respectively, and change their linear model into a deep neural network. Following Zheng et al (2013) and Chen et al (2015b), we use convolution neural networks to achieve local feature combination and LSTM to learn global sentence-level features, respectively. The resulting model is a word-based neural segmenter that can leverage rich embedding features.…”
Section: Introductionmentioning
confidence: 99%
“…We replace the discrete word and character features of Zhang and Clark (2007) with word and character embeddings, respectively, and change their linear model into a deep neural network. Following Zheng et al (2013) and Chen et al (2015b), we use convolution neural networks to achieve local feature combination and LSTM to learn global sentence-level features, respectively. The resulting model is a word-based neural segmenter that can leverage rich embedding features.…”
Section: Introductionmentioning
confidence: 99%
“…However, we employed a different training objective. Chen et al (2015) employed a max-margin objective, however, while they found this objective yielded better results, we observed that maximum-likelihood yielded better segmentation results in our experiments 1 . Additionally, we sought to integrate their model with a logbilinear CRF, which uses a maximum-likelihood training objective.…”
Section: Lstm For Word Segmentationmentioning
confidence: 46%
“…We propose a model that integrates the best Chinese word segmentation system (Chen et al, 2015) using an LSTM neural model that learns representations, with the best NER model for Chinese social media (Peng and Dredze, 2015), that supports training neural representations by a log-bilinear CRF. We begin with a brief review of each system.…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Chen et al (2015b), a standard bi-LSTM model (Graves, 2008) is used to assign segmentation label for each character. As shown in Figure 1, our model consists of a representation layer and a scoring layer.…”
Section: Concatmentioning
confidence: 99%